Indonesian Oil Palm Export Market Share and Competitiveness to European Union Countries: Is The Roundtable on Sustainable Palm Oil (RSPO) Influential? - Hansen Tandra; Arif Imam Suroso; Yusman Syaukat; Mukhamad Najib (Jurnal Manajemen & Agribisnis, 2021)
The European Union is one of the main export destinations for Indonesian palm oil. However, this area requires the sustainable development of palm oil products. Four countries from the European Union region are consistently export destinations for palm oil: Netherlands, Italy, Germany and Spain. RSPO exists as one of the institutions that ensure sustainable development in palm oil production. This study aims to analyze whether there were differences before and after implementation of RSPO in export market share and the competitiveness of CPO and RPO exports to the Netherlands, Italy, Germany, and Spain. The analysis was carried out during 1995-2020 using the paired sample t-test and the Wilcoxon signed-rank test. The analysis results show that there are differences in the export market share and competitiveness of Indonesian CPO exports to the Netherlands, Italy, Spain and Germany. The same finding was also found in RPO, especially in Indonesia's export market share. However, there is no difference in the export market share and competitiveness of Indonesian RPO exports to the Netherlands before and after implementing the RSPO in 2008. Keywords: european union, export market share, export competitiveness, palm oil